2017
DOI: 10.1016/j.ocemod.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of synthetic abyssal hill roughness on resolved motions in numerical global ocean tide models

Abstract: Global models of seafloor topography have incomplete and inconsistent resolution at horizontal wavelengths less than about 10-20 km, notably due to their inability to resolve abyssal hills in areas unsurveyed by ships (that is, about 90% of the global seafloor). We investigated the impact of this unresolved bottom roughness on global numerical simulations of the HYbrid Coordinate Ocean Model (HYCOM) that are forced exclusively by the M2 and K1 internal tides. Simulations were run with horizontal resolutions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Although mode‐1 internal tides are mainly generated by steep topographic features (Egbert & Ray, , ; Zhao et al, ), higher‐mode internal tides may be generated by the wide‐spreading small‐scale bottom features. The small‐scale gentle topographic features such as abyssal seamounts are ubiquitous in the ocean (Lefauve et al, ; Timko et al, ; Zhang et al, ). My satellite results show that these small‐scale topographic features are prone to generate higher‐mode internal tides (mode‐2 in this paper).…”
Section: Discussionmentioning
confidence: 99%
“…Although mode‐1 internal tides are mainly generated by steep topographic features (Egbert & Ray, , ; Zhao et al, ), higher‐mode internal tides may be generated by the wide‐spreading small‐scale bottom features. The small‐scale gentle topographic features such as abyssal seamounts are ubiquitous in the ocean (Lefauve et al, ; Timko et al, ; Zhang et al, ). My satellite results show that these small‐scale topographic features are prone to generate higher‐mode internal tides (mode‐2 in this paper).…”
Section: Discussionmentioning
confidence: 99%
“…In Timko et al (2017), the statistical abyssal hill roughness was employed in HYCOM simulations of the internal tides, set up under the same simplified conditions used in Arbic et al (2004) and Simmons et al (2004b), to examine the extra explicitly resolved internal tide activity arising from the small-scale roughness missing in global bathymetric datasets. Timko et al (2017) found that the roughness does indeed increase internal tide generation and energy levels, especially in the higher vertical modes that are generated by smaller-scale topography (St. Laurent and Garrett, 2002;Simmons et al, 2004b). Fig.…”
Section: Challenges For the Futurementioning
confidence: 99%
“…13.42 shows the small-scale roughness that we introduce through the Goff and Arbic (2010) and Goff (2010) work, as it appears once filtered down to 1/12.5 horizontal resolution. The method employed by Timko et al (2017) to add statistical roughness to a global internal tide model could be adapted to researchers studying other phenomena, in other models, and with different grid resolutions. In fact, in regional models with higher resolutions than the 1/12.5 and 1/25° resolutions used in Timko et al (2017)'s global models, the effects of the statistical roughness will be greater because as resolution increases the radius of the smoother that must be applied to put the raw statistical bathymetry onto a grid will decrease.…”
Section: Challenges For the Futurementioning
confidence: 99%
See 2 more Smart Citations